The psychological ownership act as mediating role on the relationship between employee motivation factors and work performance: a perspective of banking sectors in Malaysia / Kamalesh Ravesangar, Rajendran Muthuveloo and Teoh Ai Ping - Ravesangar, Kamalesh; Muthuveloo, Rajendran; Ai Ping, Teoh (2018)
Aim: The aim of the article is to emphasize on the influences of motivated employees with the high level of psychological ownership towards optimizing the work performance. This research also stressed the importance of the psychological ownership as mediating role on the relationship between employee motivation factors and work performance among the workers in the banking sectors, Malaysia. This study was conducted to find out the issues pertaining employees’ work performance based on poor service quality, critical work stress, high employee turnover rate, poor communication, inflexibility in Malaysian banking sectors. Thus, this research bring to new perspective on the employees’ work performance related issues which helps banks to improve intrinsic and extrinsic motivating factors to increase employees’ work performance through strong ownership. Furthermore, it is essential for banks to take serious attention towards the issues related since banks are experiencing critical level of poor employees’ performance which indirectly affected the overall organization performance as well. Work performance in this study consist of three dimensions comprise of task performance, contextual performance and adaptive performance. Employee motivation includes the benefits, job environment, job empowerment and recognition. Based on the research gap identified via a thorough literature review and Herzberg’s theory factors as predictor of motivation, a conceptual framework was developed. It is expected that the influence of psychological ownership will have significant effect towards employee motivation and work performance and the research findings would assist the bank management to formulate effective strategy towards optimization of its work performance that is crucial for business sustainability.